Rebooting the European Union's Net Zero Industry Act - Simone Tagliapietra; Reinhilde Veugelers; Jeromin Zettelmeyer (Bruegel, 2023)
In March 2023, the European Commission published a legislative proposal for an EU response to the US Inflation Reduction Act: the Net Zero Industry Act (NZIA). It is an unconvincing policy proposal, both for what is in it and for what is not in it. The proposal has five problematic aspects. First, it takes a top-down approach, in which specific technologies are selected for preferential treatment. Preferable would be a technology-neutral approach open to all current and future technologies that help tackle the net-zero challenge. Second, its blanket 40 percent self-sufficiency benchmark for EU domestic cleantech manufacturing by 2030 sends a protectionist signal, is poorly defined and does not reflect the differences in EU capacity in the cleantech sector. Third, it relies on the acceleration of permitting procedures as the main policy instrument, although this is not the main obstacle to cleantech investment in the EU. Fourth, it proposes more strategic use of public procurement. While this is an objective to be supported, the specific proposals are likely to be ineffective because of the way they are designed. Fifth and not least, the NZIA would lack a governance structure that would ensure effective implementation. In addition, the NZIA does not tackle three critical issues. It does not address investment obstacles related to failures of the single market. It does not tackle the coordination problem at the core of developing an EU green industrial policy. Finally, it does not develop an EU-level funding strategy, but rather relies on state aid, with the related risk of fragmentation. The European Parliament and EU countries in the Council of the EU should reboot the proposal and refocus its objectives, sharpening its limited instruments, improving its governance, and adding financial incentives to ensure implementation. In parallel, the EU should develop a broader green industrial policy strategy that leverages the single market in a credible manner, building a solid new governance framework and a new EU-level funding approach.
Keywords: 330